RUU Perampasan Aset bagi Pelaku Tindak Pidana Korupsi dalam Perspektif Tujuan Pemidanaan dan HAM: Analisis Normatif - Iskandar Iskandar; Taufik Hidayat; Hamdani Nugraha; Ryan Fachryan Lesmana Putra (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Corruption in Indonesia has become deeply rooted in society, even though various laws have attempted to stem the tide of this crime. The presence of the Asset Forfeiture Bill offers a glimmer of hope, but continues to spark debate. Normative juridical methods with statutory, conceptual and comparative approaches are used in this research. The conceptual approach understands the purpose of criminal punishment, the legislative approach examines the provisions of the Asset Forfeiture Bill, and the comparative approach compares corruption eradication practices. The Asset Forfeiture Bill plays a strategic role in strengthening corruption eradication in Indonesia, in line with the objectives of criminal punishment: providing a deterrent effect, preventing similar crimes, rehabilitating perpetrators, and recovering state losses. The non-conviction-based approach accelerates asset recovery while upholding legality, proportionality, and human rights protection.